Recent Insights into Long Bone Development: Central Role of Hedgehog Signaling Pathway in Regulating Growth Plate - Haraguchi, Ryuma (Int J Mol Sci, 2019)
The longitudinal growth of long bone, regulated by an epiphyseal cartilaginous component known as the “growth plate”, is generated by epiphyseal chondrocytes. The growth plate provides a continuous supply of chondrocytes for endochondral ossification, a sequential bone replacement of cartilaginous tissue, and any failure in this process causes a wide range of skeletal disorders. Therefore, the cellular and molecular characteristics of the growth plate are of interest to many researchers. Hedgehog (Hh), well known as a mitogen and morphogen during development, is one of the best known regulatory signals in the developmental regulation of the growth plate. Numerous animal studies have revealed that signaling through the Hh pathway plays multiple roles in regulating the proliferation, differentiation, and maintenance of growth plate chondrocytes throughout the skeletal growth period. Furthermore, over the past few years, a growing body of evidence has emerged demonstrating that a limited number of growth plate chondrocytes transdifferentiate directly into the full osteogenic and multiple mesenchymal lineages during postnatal bone development and reside in the bone marrow until late adulthood. Current studies with the genetic fate mapping approach have shown that the commitment of growth plate chondrocytes into the skeletal lineage occurs under the influence of epiphyseal chondrocyte-derived Hh signals during endochondral bone formation. Here, we discuss the valuable observations on the role of the Hh signaling pathway in the growth plate based on mouse genetic studies, with some emphasis on recent advances.